2023
DOI: 10.1161/circinterventions.122.012451
|View full text |Cite
|
Sign up to set email alerts
|

Amputation After Endovascular Therapy With and Without Intravascular Ultrasound Guidance: A Nationwide Propensity Score–Matched Study

Abstract: Background: Intravascular ultrasound (IVUS) provides precise intravascular information during endovascular therapy (EVT). However, the clinical efficacy of IVUS in patients who undergo EVT remains unknown. The present study aimed to determine whether the use of IVUS-guided EVT is associated with better clinical outcomes in a real-world setting. Methods: Using the Japanese Diagnosis Procedure Combination administrative inpatient database from April 2014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…13 In fact, this study demonstrated that IVUS was used in 65.7% of cases, which was similar to the frequency reported by the Diagnosis Procedure Combination in Japan between 2014 and 2019. 14 In the current study, we reported the baseline characteristics and frequency of IVUS use by arterial regions, and our results may reflect the potential of IVUS use for contemporary AI-and FP-EVT. | 281 Furthermore, our results showed that IVUS was more frequently used in treatment with antirestenotic devices, including DES, DCB, and covered stents.…”
Section: Summary Of the Current Studymentioning
confidence: 72%
See 1 more Smart Citation
“…13 In fact, this study demonstrated that IVUS was used in 65.7% of cases, which was similar to the frequency reported by the Diagnosis Procedure Combination in Japan between 2014 and 2019. 14 In the current study, we reported the baseline characteristics and frequency of IVUS use by arterial regions, and our results may reflect the potential of IVUS use for contemporary AI-and FP-EVT. | 281 Furthermore, our results showed that IVUS was more frequently used in treatment with antirestenotic devices, including DES, DCB, and covered stents.…”
Section: Summary Of the Current Studymentioning
confidence: 72%
“…Better assessments using IVUS could potentially help physicians to select and manage superior procedural strategies and reduce the risks of amputation or major adverse limb events. 10,14 However, the reference vessel diameter measured by IVUS has been reported to be larger than that measured by angiography, and larger balloon selection might lead to POCs, such as peripheral embolism and vascular rupture. 18 In addition, it has been reported that complications increase with procedural time extension.…”
Section: Ivus and Pocsmentioning
confidence: 99%
“…Fortunately, there has recently emerged data supporting the benefit of IVUS in lower extremity revascularization, and as such, this analysis is timely as this nascent field continues to grow. In this edition of Circulation: Cardiovascular Interventions, Setogawa et al 4 examine the characteristics and outcomes of patients undergoing endovascular therapy (EVT), stratified by the use of IVUS. This analysis uses a large Japanese administrative claims database with available procedural information for patients undergoing EVT from 2014 to 2019.…”
Section: See Article By Setogawa Et Almentioning
confidence: 99%
“…The use of IVUS was associated with a lower incidence of 12-month amputation, as well as a lower risk of stent grafting and bypass surgery. 9 A recent consensus document was published outlining clinical areas where the use of peripheral IVUS would be appropriate. 10 Detection of residual stenosis, dissection detection, and determination of next therapeutic step were all given appropriate designations for the use of peripheral IVUS in the femoropopliteal segment.…”
mentioning
confidence: 99%